2016
DOI: 10.1177/2325967116s00071
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar Collateral Ligament Repair with Internal Brace Augmentation

Abstract: Objectives:Objective: Our purpose is to describe a novel surgical technique for Ulnar Collateral Ligament repair in the young adolescent, and present the clinical results of a retrospective cohort of patients. We hypothesized that using an internal brace to augment the repair of the native ulnar collateral ligament would allow for a more aggressive physical therapy protocol and ultimately facilitate both an expeditious return to sport and a high level of patient satisfaction.Methods:Methods: After obtaining IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…One final consideration and caution: These biomechanical results do not suggest any effect on a patient’s clinical outcome. However, Walters et al 34 showed a 92% return to play at 6 months, which is a higher rate than most studies on UCL reconstruction. However, the long-term performance remains unknown.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…One final consideration and caution: These biomechanical results do not suggest any effect on a patient’s clinical outcome. However, Walters et al 34 showed a 92% return to play at 6 months, which is a higher rate than most studies on UCL reconstruction. However, the long-term performance remains unknown.…”
Section: Discussionmentioning
confidence: 77%
“…6,12,13,17,26,28 Although nonoperative management is an option, faster return to play makes operative care of UCL ruptures desirable for both patients and parents. 1,15,20,34…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the anticipated length of recovery depends on the procedure. Position players typically return to play at around 6 months after a UCL repair, 6,7,13,17 as compared with 9 to 12 months after a UCL reconstruction. 1,12 The anticipated length of recovery also depends on whether the patient is a pitcher and wants to return to pitching.…”
Section: Length Of Recoverymentioning
confidence: 99%
“…Multiple studies now published on clinical outcomes of MUCL repair with internal brace augmentation, [1][2][3][4][5][6]10 and a recent study by Dugas et al 3,4 reported favorable outcomes for 111 patients who had a 92% return to play rate at a mean time of 6.7 months.…”
Section: Surgical Techniquesmentioning
confidence: 99%